Manual on Biotic Stress Resistance Evaluation (First Edition) - Telebanco-Yanoria, Mary Jeanie; Atienza-Grande, Genelou; Jonson, Gilda; Almazan, Maria Liberty; Bernal, Carmencita; Pangesti, Nurmi; Pacia, Jocelyn; Castilla, Nancy; Carvajal, Raphael; Ortega, Kendrix; Natulan, Rafael Luis; Valenzuela, Ma Michelle; et al. (International Rice Research Institute, 2025)
Overview